Strategies to approximate random sampling and assignment - Dattalo, Patrick (New York ; Oxford : Oxford University Press, 2010)
This book is a single source of a diverse set of tools that will maximize a study's validity when RS and RA are neither possible nor practical. Readers are guided in selecting and implementing an appropriate strategy, including exemplar sampling, sequential sampling, randomization tests, multiple imputation, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sampling (Statistics); Social service -- Statistical methods